A developmental neuroscience perspective on affect-biased attention. (October 2016) - Morales, Santiago; Fu, Xiaoxue; Pérez-Edgar, Koraly E.
Highlights: We place affect-biased attention within a developmental neuroscience framework. We suggest that affect-biased attention serves as a domain general mechanism. Affect-biased attention broadly shapes socioemotional trajectories across development. We review the developmental neurocognitive mechanisms of affect-biased attention. A proposed model helps place affect-biased attention in a developmental context. Abstract: There is growing interest regarding the impact of affect-biased attention on psychopathology. However, most of the research to date lacks a developmental approach. In the present review, we examine the role affect-biased attention plays in shaping socioemotional trajectories within a developmental neuroscience framework. We propose that affect-biased attention, particularly if stable and entrenched, acts as a developmental tether that helps sustain early socioemotional and behavioral profiles over time, placing some individuals on maladaptive developmental trajectories. Although most of the evidence is found in the anxiety literature, we suggest that these relations may operate across multiple domains of interest, including positive affect, externalizing behaviors, drug use, and eating behaviors. We also review the general mechanisms and neural correlates of affect-biased attention, as well as the current evidence for the co-development of attention and affect. Based on the reviewed literature, we propose a model that may help us better understand the nuances of affect-biased attention across development. The model may serve as a strong foundation for ongoing attempts to identify neurocognitive mechanisms and intervene with individuals at risk. Finally, we discuss open issues for future research that may help bridge existing gaps in the literature.